994OLenvatinib (LEN) and pembrolizumab (PEMBRO) in advanced endometrial cancer (EC). (1st October 2019) - Makker, V; Taylor, M H; Aghajanian, C; Oaknin, A; Mier, J; Cohn, A L; Marin, M Romeo; Lorenzo, R Bratos; Brose, M S; DiSimone, C; Messing, M J; Stepan, D E; et al.
Abstract: Background: LEN is a multikinase inhibitor of VEGFR 1–3, FGFR 1–4, PDGFRα, RET, and KIT. PEMBRO is an anti-PD-1 antibody. We report final results of a cohort of patients (pts) with metastatic EC (data cutoff, Jan. 10, 2019) as part of an ongoing phase 1b/2 study evaluating LEN + PEMBRO in pts with selected solid tumours. Methods: In this cohort of a multicenter, open-label study, pts with histologically confirmed metastatic EC and measurable disease who received ≤2 prior chemotherapies (unless discussed with the sponsor) were administered LEN (20 mg PO QD) plus PEMBRO (200 mg IV Q3W). Tumour assessments for the primary phase 2 endpoint (objective response rate at 24 weeks [ORRWK24 ]) and secondary endpoints were evaluated by investigators per immune-related (ir)RECIST. Secondary endpoints included ORR, progression-free survival, overall survival, and duration of response. Tumour responses were also assessed by independent imaging reviewers per irRECIST, RECIST 1.1, and modified RECIST 1.1, and by investigators per mRECIST 1.1. Results: At data cutoff, 108 pts with previously treated (1 regimen: 53%; >1 regimen: 47%) EC (endometrioid: 51%; serous: 32%; FIGO grade 3: 70%) were enrolled and had a median follow-up of 18.7 months. 13% of pts had high microsatellite instability (MSI-H) or mismatch-repair deficient (dMMR) status. Efficacy outcomes are summarized in the table. Treatment-related adverse events (TRAEs) occurred in 105 (97%) pts (97 [90%] ≤ grade 3, 8 [7%] ≥ grade 4). TRAEs led to study-drug interruption of one or both drugs in 78 (72%) pts and dose reductions of LEN in 70 (65%) pts; 20 (19%) pts discontinued one or both drugs due to a TRAE. The most common ≥ grade 3 TRAEs were hypertension (32%), fatigue (8%), and diarrhea (7%). Conclusions: The LEN + PEMBRO combination showed promising antitumor activity in metastatic EC regardless of MSI/MMR status. Treatment was generally well tolerated, and no new safety signals emerged. A phase 3 study in advanced EC is underway (NCT03517449). Clinical trial identification: NCT02501096. Editorial acknowledgement: Jeffrey K. Bratz, PhD of Oxford PharmaGenesis, Newtown, PA was funded by Eisai Inc. Legal entity responsible for the study: Eisai Inc. Funding: Eisai Inc. and Merck Sharp & Dohme Corp., a subsidiary of Merck & Co., Inc., Kenilworth, NJ, USA. Disclosure: V. Makker: Non-remunerated activity/ies: AstraZeneca; Honoraria (self), Non-remunerated activity/ies: Eisai; Honoraria (self), Non-remunerated activity/ies: Merck; Non-remunerated activity/ies: Lilly; Honoraria (self), Non-remunerated activity/ies: Karyopharm; Honoraria (self), Non-remunerated activity/ies: Takeda; Non-remunerated activity/ies: Genentech. M.H. Taylor: Research grant / Funding (institution): BioAlta; Honoraria (self), Advisory / Consultancy, Speaker Bureau / Expert testimony, Travel / Accommodation / Expenses: Bristol-Myers Squibb; Honoraria (self), Advisory / Consultancy, Travel / Accommodation / Expenses: Array Biopharma; Honoraria (self), Advisory / Consultancy, Speaker Bureau / Expert testimony, Travel / Accommodation / Expenses: Eisai; Honoraria (self), Travel / Accommodation / Expenses: Bayer; Honoraria (self), Advisory / Consultancy, Travel / Accommodation / Expenses: LOXO; Honoraria (self), Advisory / Consultancy, Travel / Accommodation / Expenses: Blueprint; Honoraria (self), Advisory / Consultancy: Arquele; Honoraria (self), Advisory / Consultancy: Novartis. C. Aghajanian: Advisory / Consultancy: Tesaro; Advisory / Consultancy: Immunogen; Advisory / Consultancy, Research grant / Funding (self): Clovis; Honoraria (self): Mateon Therapeutics; Advisory / Consultancy: Cerulean Pharma; Research grant / Funding (self): Genentech. A. Oaknin: Travel / Accommodation / Expenses: Roche; Travel / Accommodation / Expenses: AstraZeneca; Research grant / Funding (institution), Travel / Accommodation / Expenses: PharmaMar; Research grant / Funding (institution), Travel / Accommodation / Expenses: Clovis Oncology; Honoraria (self), Research grant / Funding (institution): Tesaro; Honoraria (self), Research grant / Funding (institution): Immunogen; Research grant / Funding (institution): Eisai Ltd.; Research grant / Funding (institution): Merck Sharp & Dohme de España SA; Honoraria (self): Genmab; Research grant / Funding (institution): AbbVie Deutschland; Research grant / Funding (institution): Millennium Pharma; Research grant / Funding (institution): Regeneron Pharmaceuticals; Research grant / Funding (institution): Ability Pharmaceuticals; Research grant / Funding (institution): Advaxis Inc; Research grant / Funding (institution): Aeterna Zentaris; Research grant / Funding (institution): Amgen SA; Research grant / Funding (institution): Aprea Therapeutics AB; Research grant / Funding (institution): F. Hoffman - La Roche Ltd. M. Romeo Marin: Advisory / Consultancy: Tesoro; Advisory / Consultancy, Non-remunerated activity/ies: Roche; Speaker Bureau / Expert testimony: AstraZeneca. M.S. Brose: Honoraria (self): Eisai. D.E. Stepan: Full / Part-time employment: Formerly of Eisai Inc. C.E. Dutcus: Leadership role, Full / Part-time employment: Eisai Inc. J. Wu: Full / Part-time employment: Eisai Inc. E.V. Schmidt: Full / Part-time employment: Merck & Co Inc. R.J. Orlowski: Full / Part-time employment: Merck & Co Inc. P. Sachdev: Full / Part-time employment: Eisai Inc. R. Shumaker: Full / Part-time employment: Eisai Inc. A. Casado Herraez: Research grant / Funding (institution), Travel / Accommodation / Expenses: PharmaMar. All other authors have declared no conflicts of interest.